Peritoneal adhesions. Experimental study: Role of deitonized surfaces in formation of adhesions. Conduct in such cases. Test of a prophylactic anti-adhesion treatment. - Lesina, Elmer; Delgado, Fernando; Criado, Francisco J; Miraglia, Domingo; Martínez, Jorge (Cirugía del Uruguay, 1972)
The author studies the role of deperitonized surfaces in the formation of adhesions and presents the results of an attempt to establish profila- ctic antiadhesion treatment for such cases. The results seem to point out that defects of the parietal peritoneum should not be closed and that Trasylol is effective in the prevention of ad1íesions. Furthermore it shows that visceral deperitonized areas lead inevitably to the formation of adhesions.